"Virtus": fundamento, clave y eje de la educación política en la Edad Moderna : La válida respuesta de Thomas Fitzherbert (1552-1640) a la deconstrucción maquiaveliana = Virtus : foundations, keystone and axis of Early Modern political education : The valid response of Thomas Fitzherbert (1552-1640) to Machiavellian deconstruction - Viguria-Guerendiáin, Lía (Anuario de historia de la Iglesia, 2019)
1513 opened a subversive stage in the history of political thought. Machivelli abandoned the reference to God and nature, the basis of the anthropological and social order from time immemorial. In the field of pedagogy, Machiavelli shamelessly taught degrading abilities to his partisan politicians with a view to staying in power. This degradation affected Thomas Fitzherbert intellectual and personally. Resisting this anthropocentric reclusion, he wielded the pen as a weapon to write An sit utilitas in scelere . His ends were to claim the power of virtus as dignity, as a way and means for the ruler. Fitzherbert spoke aloud with ink, even bleeding ink. He emboldened himself to hold the flag of the virtus, the unique arena in which every prince is worth training.